A new heuristic method for solving two machine flow shop with job block, transportation time and final assemble on a single machine without job block - Janaki, E.; Ismail, A. Mohamed; kumar, M. Prem (AIP conference proceedings, 2024)
Processing jobs in different location with minimum completion time and customer’s satisfaction is a big task for a production and planning engineers in an industry. In this paper, we propose a new heuristic method for solving flow shop machine with permutation and single machine situated at different locations. To obtain an optimal sequence, we consider a equivalent job for job block on giving a set of jobs processed on first two machines with transportation time by using Johnson’s algorithm. To assemble these jobs, we introduce single machine with due date and obtain minimum makespan by using heuristic methods. Numerical examples are given.